Cyclohexylethyl-Engineered Acceptor Enables Uniform Donor–Acceptor Morphology and over 20% Efficient Layer-by-Layer Organic Solar Cells - Luo, Mei; Zhao, Siyu; Kong, Lingchen; He, Qihua; Chen, Mingqing; Yuan, Xiyue; Li, Mingke; Luo, Xuanang; Qi, Weitao; Song, Bohao; Lu, Guanghao; Zhang, Zesheng; et al. (Advanced Functional Materials, 2026)
Layer-by-layer (LBL) technique offers a promising platform for optimal vertical phase separation in organic solar cells (OSCs). Nevertheless, the realization of high-performance LBL-OSCs is fundamentally limited by solvent-induced swelling during deposition, a process that promotes uncontrolled donor–acceptor interdiffusion, thereby constraining device performance. To address this challenge, we introduce a molecular design strategy that incorporates a novel third component, BTA-CyH. Engineered with a rigid cyclohexane unit at the terminus of the N-side chain in benzotriazole unit, the BTA-CyH acceptor leverages steric hindrance and self-assembly to precisely modulate the interpenetration dynamics of the acceptor during LBL film formation. Incorporating 10 wt.% BTA-CyH into the L8-BO layer serves a dual function: it enhances donor–acceptor miscibility to promote more D/A (donor/acceptor) interfaces and efficient exciton dissociation, while simultaneously regulating crystallization dynamics by suppressing excessive aggregation and fostering improved molecular ordering and crystallinity. Consequently, the ternary OSCs achieve a remarkable power conversion efficiency (PCE) of 19.73%. With Ph-4PACz as the hole extraction layer, over 20% efficiency is demonstrated in D18/L8-BO:BTA-CyH-based device. This work highlights rational side-chain engineering as a powerful and generalizable strategy for manipulating vertical composition profiles and interfacial nanostructures in LBL-OSCs, paving the way for further advances in sequentially fabricated high-performance OSCs.
CRIS-Team Scopus Importer:2026-03-20
Keywords: cyclohexylethyl-substituted; non-fullerene acceptors; organic solar cells; power conversion efficiencies; ternary components